Abundance and utilization of sea hares (dolabella aurecularia) in Sanipaan Shoal, Davao Gulf - Millena, May Zel T. (2006)
A study was conducted to determine the abundance and utilization of sea hares in Sanipaan Shoal. Their food preference, habitat, predator and reproductive biology were also observed. Dolabella auricularia was the only species found in Sanipaan Shoal. From the seven 100m transects established, a total of 136 individuals was recorded during an 8-month period in 2004 particularly during the months of January, February, April, July and December. Transect 1, which has thick seagrass as substrate yielded the highest sea hare population with 56% followed by transect 7 (characteristically seagrass to coral rubble bed) with 30%. Lesser hares were noted in Transects 2 and 6 (7% to 8%), which are characterized by coral rubble to seagrass as substrate, respectively. while only one sea hare was recorded from Transect 4 (coral rubble to patches), none was found in Transects 3 and 5, which are predominantly sandy and coral rubble beds. Thalassia sp. and Gracilaria sp. were the seagrass species serving as both shelter and food for the sea hares, which lay their eggs on the bases of the seagrasses. No predators were noted to impinge on the sea hare population during the study period except humans who harvest the eggs and adults for consumption. The unregulated harvest of sea hares by gleaners is said to cause the low abundance of sea hares in the island